Online Health Information–Seeking Behaviors Among the Chongqing Population: Cross-Sectional Questionnaire Study - Honghui Rong; Lu Lu; Miao He; Tian Guo; Xian Li; Qingliu Tao; Yixin Li; Chuanfen Zheng; Ling Zhang; Fengju Li; Dali Yi; Enyu Lei; et al. (JMIR Formative Research)
Abstract BackgroundWith the rapid development of the internet and its widespread use, online health information–seeking (OHIS) has become a popular and important research topic. Various benefits of OHIS are well recognized. However, OHIS seems to be a mixed blessing. Research on OHIS has been reported in Western countries and in high-income regions in eastern China. Studies on the population in the western region of China, such as Chongqing, are still limited. ObjectiveThe aim of the study was to identify the prevalence, common topics, and common methods of health information–seeking and the factors influencing these behaviors among the Chongqing population. MethodsThis cross-sectional questionnaire study was conducted from September to October 2021. A web-based questionnaire was sent to users aged 15 years and older in Chongqing using a Chinese web-based survey hosting site (N=14,466). Data on demographics, web-based health information resources, and health topics were collected. Factors that may influence health literacy were assessed using the ResultsA total of 67.1% (9704/14,466) of the participants displayed OHIS behaviors. Participants who were younger, had a higher educational level, and worked as medical staff or teachers were more likely to engage in OHIS, while those living in rural areas, ethnic minorities, and farmers were less likely to seek health information on the web (P ConclusionsOHIS is prevalent in Chongqing. Further research could be performed based on the influencing factors identified herein and high-priority, effective ways of improving the OHIS behaviors of the Chongqing population.